East Side Story: Historical Pollution and Persistent Neighborhood Sorting - Stephan Heblich; Alex Trew; Yanos Zylberberg (Center for Economic Studies and ifo Institute (CESifo), 2016)
Why are the East sides of former industrial cities like London or New York poorer and more deprived? We argue that this observation is the most visible consequence of the historically unequal distribution of air pollutants across neighborhoods. In this paper, we geolocate nearly 5,000 industrial chimneys in 70 English cities in 1880 and use an atmospheric dispersion model to recreate the spatial distribution of pollution. First, individual-level census data show that pollution induced neighborhood sorting during the course of the nineteenth century. Historical pollution patterns explain up to 15% of withincity deprivation in 1881. Second, these equilibria persist to this day even though the pollution that initially caused them has waned. A quantitative model shows the role of non-linearities and tipping-like dynamics in such persistence.
Keywords: R23; Q53; N90; 330; neighborhood sorting; historical pollution; deprivation; persistence; environmental disamenity